Does Early Treatment Improve Clinical Outcome of Class II Patients? A Retrospective Study - Roland Männchen; Marco Serafin; Rosamaria Fastuca; Alberto Caprioglio (MDPI AG, 2022)
The present study was carried out to evaluate the benefits from one-phase Class II Early Treatment (ET) using extraoral forces and functional appliances but without intermaxillary forces and eventual lower leeway space preservation compared to two-phase Class II Late Treatment (LT) with the need for extractions and full fixed appliances as well as lower incisor proclination. The ET group (n = 239, 115 M, 124 F, mean age 10.6 ± 1.2 years), with first premolars not in contact and the second deciduous lower molars preserved, was compared to the LT group (n = 288, 137 M, 151 F, mean age 12.4 ± 1.5 years). The ET group was first treated with headgears, growth guide appliances, or Teuscher activators and, in borderline crowding cases, with lower space maintenance by a lingual arch, lip bumper, or fixed utility arch. The LT group and the second phase of ET were treated with full fixed appliances including intermaxillary forces such as Class II elastics or noncompliance devices; headgear and a growth guide appliance were also used. Cephalograms and plaster models were taken before (T1) and after treatment (T2) to calculate cephalometric changes and space balance discrepancies. The differences between T1 and T2 were analyzed by a t-test for normally distributed data and by the Mann-Whitney Test for nonnormally distributed data at a level of p < 0.05. The groups were defined as statistically homogeneous at T1. A statistical analysis showed that the ET group (mean treatment time 35.3 ± 13.3 months) was significantly associated with a 22.2% lower extraction rate, 15.9% less need for a full fixed appliance, and more than 5° less incisor proclination in the nonextraction cases compared to the LT group (mean treatment time 25.9 ± 8.1 months); treatment time significantly increased in the ET group compared to the LT group. Early Class II treatment resulted in a significant treatment effort reduction in more than one third of the patients and less lower incisor proclination, even if it clinically increased treatment time.